Heterogeneous health effects of medical marijuana legalization: Evidence from young adults in the United States - CHAY, Junxing (Institutional Knowledge at Singapore Management University, 2022)
Legalizing marijuana for medical purposes is a longstanding debate. However, evidence of marijuana's health effects is limited, especially for young adults. We estimate the health impacts of medical marijuana laws (MML) in the U.S. among young adults aged 18–29 years using the difference-in-differences method and data from the Behavioral Risk Factors Surveillance System. We find that having MMLs with strict regulations generate health gains, but not in states with lax regulations. Our heterogeneity analysis results indicate that individuals with lower education attainments, with lower household income and without access to health insurance coverage gain more health benefits from MML with strict regulations than from MML with lax regulations. The findings suggest greater net health gains under strict controls concerning marijuana supply and access.